2015
DOI: 10.5194/cp-11-647-2015
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene–Holocene ground surface heat flux changes reconstructed from borehole temperature data (the Urals, Russia)

Abstract: Abstract. We use geothermal reconstruction of the ground surface temperature (GST) history early obtained in the Middle Urals to determine the surface heat flux (SHF) history over the past 35 kyr. A new algorithm of GST-SHF transformation was applied to solve this problem. The timescale of geothermal reconstructions has been corrected by comparing the estimated heat flux and annual insolation at the latitude of 60 • N. The consistency of SHF and insolation changes on the interval 35-6 kyr BP with the linear co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…Comparison to other temperature data Figure 4 shows the trends of the resulting temperature histories at Mamontov Klyk and Sardakh Island in comparison to other local records from the region as well as to larger scale temperature trends. To be able to compare these records to the geothermal reconstruction, their annually resolved time series were averaged using the non-uniform running windows of the minimum event resolution referenced to the year 2011/2012 CE [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison to other temperature data Figure 4 shows the trends of the resulting temperature histories at Mamontov Klyk and Sardakh Island in comparison to other local records from the region as well as to larger scale temperature trends. To be able to compare these records to the geothermal reconstruction, their annually resolved time series were averaged using the non-uniform running windows of the minimum event resolution referenced to the year 2011/2012 CE [18].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we choose methods that do not specify high-frequency changes in the past. In addition, a procedure of averaging with non-uniform running windows should be used whenever comparing temperature time series of constant temporal resolution (such as annual observations) to geothermal reconstructions [18]. To estimate the past surface temperature history T j from the borehole temperature observations, two inverse methods (LSQR and Particle Swarm) were used with the forward soil model to optimize a surface temperature history for each of the borehole sites (Sects.…”
Section: Optimizationmentioning
confidence: 99%
“…(Demezhko and Shchapov, 2001) studied a ∼ 5 km deep borehole in the Urals, Russia, and found a postglacial warming of 12-13 K, with basal temperatures below the melting point of ice during the LGM. This was confirmed by recent work indicating that temperatures in the Urals were ∼ −8 • C at the LGM (Demezhko and Gornostaeva, 2015). In this study, we shall examine all the deep-borehole temperature profiles measured in central and eastern Canada in order to determine the temperature at the base of the Laurentide Ice Sheet, which covered the area during the LGC.…”
mentioning
confidence: 66%
“…They concluded that temperatures at the base of the ice sheet in Northern Alberta were about −3 • C during the LGM. On the other hand, studies of deep boreholes in Europe lead to different conclusions for the Fennoscandian Ice Sheet which covered parts of Eurasia during the LGC (see, e.g., Demezhko and Shchapov, 2001;Kukkonen and Jõeleht, 2003;Šafanda et al, 2004;Majorowicz et al, 2008;Demezhko et al, 2013;Demezhko and Gornostaeva, 2015) . (Kukkonen and Jõeleht, 2003) analyzed heat flow variations with depth in several boreholes from the Baltic Shield and the Russian Platform and found a 8 ± 4.5 K temperature increase following the LGM.…”
mentioning
confidence: 99%
“…SHF is positive in downward direction (from the surface to depth).Being an energy expression of climate variations this heat flux contrary to temperature might be directly compared with another energy characteristics (for example with solar insolation) to identify the origin of climate changes. The algorithm of GST -SHF transformation have been developed for SHF evaluation(Demezhko, Gornostaeva, 2015a). SHF histories obtained from GST histories mentioned above are shown inFig.…”
mentioning
confidence: 99%